Age structure, growth pattern, sexual maturity, and longevity of Leptodactylus latrans (Anura: Leptodactylidae) in temperate wetlands - Lopez, Javier Alejandro (2017)
We present the first data on age structure, growth pattern, and lines of arrested growth (LAG) for Leptodactylus latrans in temperate wetlands. Based on these data, we estimate LAG periodicity, age, size at sexual maturity and longevity for this species. We also tested for differences of these parameters between sexes. The age was determined through skeletochronology. Female maturity was determined by presence of differentiated ova, while male maturity was assessed through histological analysis to evaluate spermatozoid production. To establish whether this species marks one LAG per year, eight individuals were kept one year in captivity. For each specimen, LAG was compared for different phalanges of the same toe clipped at start and end of captivity. Leptodactylus latrans marked one LAG per year, indicating a growth rhythm adjusted to a seasonal environment and mainly driven by genetic factors. Longevity was five years for both sexes and frogs reached sexual maturity during the first year, exhibiting a reproductive lifespan of four years. Sexual maturity was related to a minimal size of 60 mm or a body mass of around 33 g. There was no difference in either size or growth pattern between sexes. The von Bertalanffy growth model showed that L. latrans grows fast after metamorphosis and their growth rate strongly decreases at about three years, probably due to the increased allocation of energy to reproduction. The high growth rates and early sexual maturation of L. latrans would allow an elevated rate of population renewal.